Ultrastructural characteristics of ovine bone marrow‐derived mesenchymal stromal cells cultured with a silicon stabilized tricalcium phosphate bioceramic. Issue 11 (11th August 2017) - Desantis, Salvatore; Accogli, Gianluca; Burk, Janina; Zizza, Sara; Mastrodonato, Maria; Francioso, Edda G.; Rossi, Roberta; Crovace, Antonio; Resta, Leonardo
Abstract: Bioceramics are being used in experimental bone engineering application in association with bone marrow derived mesenchymal stem cells (BM‐MSCs) as a new therapeutic tool, but their effects on the ultrastructure of BM‐MSCs are yet unknown. In this study we report the morphological features of ovine (o)BM‐MSCs cultured with Skelite, a resorbable bioceramic based on silicon stabilized tricalcium phosphate (SiTCP), able to promote the repair of induced bone defect in sheep model. oBM‐MSCs were isolated from the iliac crest, cultured until they reached near‐confluence and incubated with SiTCP. After 48 hr the monolayers were highly damaged and only few cells adhered to the plastic. Thus, SiTCP was removed, and after washing the cells were cultured until they became confluent. Then, they were trypsinizated and processed for transmission electron microscopy (TEM) and RT‐PCR analysis. RT‐PCR displayed that oBM‐MSCs express typical surface marker for MSCs. TEM revealed the presence of electron‐lucent cells and electron‐dense cells, both expressing the CD90 surface antigen. The prominent feature of electron‐lucent cells was the concentration of cytoplasmic organelles around the nucleus as well as large surface blebs containing glycogen or profiles of endoplasmic reticulum. The dark cells had a multilocular appearance by the presence of peripheral vacuoles. Some dark cells contained endocytic vesicles, lysosomes, and glycogen aggregates. oBM‐MSCs showed different types of specialized interconnections. The comparison with ultrastructural features of untreated oBM‐MSCs suggests the light and dark cells are two distinct cell types which were differently affected by SiTCP bioceramic. Skelite cultured ovine BM‐MSCs display electron‐dense and electron‐lucent cells which are differently affected by this bioceramic. This suggests that they could play a different role in bioceramic based therapy. Abstract : Skelite cultured ovine bone marrow mesenchymal stem cells display electron‐dense and electron‐lucent cells which are differently affected by this bioceramic. This suggests that they could play a different role in bioceramic‐based therapy.